Perception and challenges towards Family Adoption Program among undergraduate students of a Medical College of Tripura: a cross-sectional study - Das, Shampa; Baidya, Subrata; Mog, Chanda; Pal, Achintya; Pal, Aparajita; Das, Paramita (International Journal Of Community Medicine And Public Health, 2025)
Background: In 2022, NMC has introduced family adoption program as part Community Medicine Curriculum to sensitize upcoming medical professionals for the health needs of community. Objectives of the study were to assess perception towards FAP among first and second professional medical students of Agartala Government Medical College of Tripura and to determine the challenges encountered by the students during family adoption visits. Methods: A cross-sectional study was conducted among 1st and 2nd Professional MBBS Students of AGMC for a period of one month. All students of 1st and 2nd Professional were included with a sample size of 250. A semi structured questionnaire was used for data collection and data were analysed using SPSS v.29. Perception towards FAP was measured with 1-5-point Likert scale where 1 being lowest and 5 being highest score. Mean score of each item was measured. Study was approved by Institutional Ethics Committee of AGMC. Results: Total 210 students had participated. Regarding perception of students towards FAP, majority agreed that it will create health awareness in community and can understand dynamics of rural setup. Communication and leadership skill can be learned and it provide an early clinical exposure to students. Students had faced multiple challenges like, families expected curative treatment but students were not eligible to provide (47.8%), language barrier (26.8%), difficulty in graining trust (26.3%) and cooperation from the families (18.7%) etc. Conclusions: Family adoption helps the students to learn communication and leadership skill and it will improve health awareness in community.